A Soft‐Elastic Reactor Inspired by the Animal Upper Digestion Tract. Issue 5 (6th April 2018) - Liu, Minghui; Xiao, Jie; Chen, Xiao Dong
Abstract: A soft‐elastic reactor is described, which was inspired by the animal upper digestion tract. The mixing is triggered by wall movements. Silicone material was selected based on previous experiences and conditioned into a standard cylindrical shape. Mixing was induced by the wall deformation triggered by the peristaltic movement, i.e., periodic protrusion towards the wall. Viscous glycerin solution served as sample material and a tracer was added to visualize the mechanisms of mixing. The fluid motion initiated by the soft‐elastic wall movement could be an interesting alternative to stirrer agitation. Pros and Cons are briefly highlighted. Due to the abundance of industrial soft‐elastic materials such as silicone, it is expected that, inspired by the soft reactors, a series of inventions in chemical reactor engineering will be offered in the near future. Abstract : Inspired by animal digestion track systems, a mixing scheme driven by an elastic wall movement could be an interesting alternative to mechanical stirrer agitation. A prototype of the soft‐elastic reactor was built and its functionality was demonstrated. The promising results can lead to further innovations in elastic reactor designs and new applications of such reactors are expected in future.